Evaluation of the Antibacterial Capacity of a New Strain of Enterococcus faecium from the Honey Bee Gut - al-shimmary, sana; Al-Thwani, Amina N. (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
The recent development of antibiotic-resistant microorganisms has been a consequence of antibiotic overuse. Today, an increasing number of antibiotic-resistant microorganisms are a threat to public health. Bacteriocin is an antimicrobial peptide with potential as an alternative to antibiotics. Recent research has shown that bacteriocins effectively inhibit the growth of bacteria that have developed resistance. Enterococcus faecium (E. faecium) is among the producers of these compounds. The study aimed to isolate and investigate  E. faecium found in the gut of honey bees and demonstrate its bacteriocin-like inhibitor substances as an inhibitory agent against multidrug-resistant (MDR) Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) growth.E. faecium was confirmed by sequencing the 16S rRNA gene. The screening involved assessing the impact of cell-free supernatant (CFS) obtained from E. faecium on the growth of MDR S. aureus and P. aeruginosa. The results reported a significant inhibition zone of 30 mm for S. aureus and 33 mm for P. aeruginosa. The optimum conditions for CFS production were as follows: the most suitable nitrogen and carbon sources were yeast extract and glucose, respectively. The optimal pH was 6, and the incubation period was 48 hours.